Translingualism and social media: The expression of intense emotions of Mongolian background immigrant women in Australia - Dovchin, Sender; Tankosić, Ana; Dryden, Stephanie (Routledge, 2022)
Drawing on digital ethnographic data analysis of social media posts by Mongolian women in Australia, this chapter aims to expand the critical discussions of the sociolinguistics of globalization by investigating how these women express themselves linguistically when they are feeling strong emotions, how they use translingualism to maintain the flow of their interactions, and how they control and overcome their feelings of discomfort, anger and humiliation when sharing their stories with each other. The manifestation of a translingual orientation in sociolinguistic academic discourse in the last decade has brought focus on the flexibility and fluidity of language and its constant interplay with notions of identity, particularly when it comes to culturally and linguistically diverse groups and individuals. What is more, large portions of our life have been transferred to social media, creating a social translingual space where migrants become encouraged to talk freely about distressing experiences in their new environments and to express their emotions through an empowering discourse. These Mongolian migrant women in Australia use translingualism strategically to keep the online interaction fluid and ongoing, to express and deal with their emotions, particularly their anger, humiliation, and frustration, and to bring themselves closer to others who understand their language and culture. Their online translingual discourses show that these women harness the resources that they have to make sense of their experiences, which brings the interlocutors together in their values, beliefs, and personalities to create shared lived experiences, rather than succumbing to pain and unhappiness in solitude.